Quantitatively measuring the influence of helium in plasma-exposed tungsten. (August 2017) - Doerner, R.P.; Baldwin, M.J.; Simmonds, M.; Yu, J.H.; Buzi, L.; Schwarz-Selinger, T.
Highlights: Tungsten samples are exposed to 3 He plasma to quantify their helium retention behavior. The retention saturates quickly with helium fluence and increases only slightly from 4.3 × 10 19 He/m 2 at 773 K, to 7.5 × 10 19 He/m 2 at 973 K. The helium content increases to 6.8 × 10 20 He/m 2 when fuzz is formed on a sample exposed at 1173 K, but the majority of the retained helium (5.1 × 10 20 He/m 2 ) is found to reside below the layer of fuzz tendrils. Abstract: Tungsten samples are exposed to 3 He plasma to quantify their helium retention behavior. The retention saturates quickly with helium fluence and increases only slightly from 4.3 × 10 19 He/m 2 at 773 K, to 7.5 × 10 19 He/m 2 at 973 K. The helium content increases dramatically to 6.8 × 10 20 He/m 2 when fuzz is formed on the surface of a sample exposed at 1173 K, but the majority of the retained helium (5.1 × 10 20 He/m 2 ) is found to reside below the layer of fuzz tendrils. Additional tungsten samples were exposed to either simultaneous, or sequential, D/He plasma, followed by TDS. Measurements show the majority of the D retained during simultaneous exposures is located in the near surface region of helium nano-bubbles. No deuterium was detected in any of the samples after the heating to 1273 K, but 67% of the helium was released from simultaneously exposed samples, and only 23% of the helium was released from the sequentially exposed samples.